Adherence to Viral Load Testing Guidelines, Barriers, and Associated Factors Among Persons Living with HIV on ART in Southwestern Uganda: a Mixed-Methods Study. - Lubega, Polly; Nalugya, Sylivia Juliet; Kimuli, Angella Namyalo; Twinokusiima, Majoreen; Khasalamwa, Mercy; Kyomugisa, Richard; Kabami, Jane; Owaraganise, Asiphas (Kabale University, 2024)
Background: Uganda adapted Viral load (VL) testing for monitoring HIV treatment success and virologic failure. However, there is a paucity of data on how the VL testing guidelines are followed in practice in HIV clinics. This study determined the adherence to national guidelines on VL testing, barriers, and associated factors in persons living with HIV (PLHIV) on ART in southwestern Uganda. Methods: We conducted a cross-sectional mixed methods study from April to May 2021 at four HIV clinics in southwestern Uganda. Patient chart review using a checklist that captured age, gender, and level of a healthcare facility, dates of ART initiation, dates VL specimens were drawn, line of ART, and patient adherence to ART was done. Continuous data were summarized using mean and median and Chi-square was used for categorical data. We performed regression analysis to determine factors associated with adherence to viral load testing guidelines at a 95% level of significance. Key informant interviews with managers of the health facility, ART clinic, and laboratory were carried out, and thematic analysis was conducted to explore barriers to adherence to VL testing guidelines. Results: The participants’ mean (SD) age was 39.9(±13.1) years, 39.5% were male, 45.8% received care at a general hospital and the median duration of ART was 5 years (IQR;3–7). Of the 395 patient charts reviewed, 317 had their VL testing (80.3%) per the guidelines (defined as up to one month post-due date). Receiving care at a hospital (aOR=2.20; 95%CI 1.30–3.70; p=0.002) and increasing patient age (aOR=1.02; 95%CI 1.02–1.06; p=0.020) were the factors associated with adhering to VL testing guidelines. Long turnaround times of VL results and insufficient VL testing kits were cited by providers as barriers. Conclusion: We found suboptimal adherence to VL testing guidelines in PLHIV on ART in southwestern Uganda. Increasing patient age and getting care at a higher-level health facility were associated with guideline-based viral VL testing. The long turnaround time of VL test results and inadequate test kits hindered compliance with VL monitoring guidelines. Strategies that target young PLHIV and lower-level health facilities, increase the stock of consumables, and Shorten VL results turnaround time are needed to improve adherence to VL testing guidelines.